Multiple Cover Formula for the Stable Pairs Theory of K3xE - Oberdieck, Georg (Institut des Hautes Études Scientifiques (IHÉS), 2021)
The count of stable pairs (Pandharipande-Thomas theory) on K3 x E is well-understood whenever the curve class is primitive over the K3 factor. I will explain how ideas of Pandharipande and Thomas can be used to remove the primitivity assumption
Audiovisuelles Material